Bond credit analysis : (Frank J. Fabozzi Associates, 2001)
Credit analysis is an important factor in judging investment value. Fundamentally sound credit analysis can offer more insight into the value of an investment and lead to greater profits. This study presents a professional framework for understanding and managing a successful corporate or municipal bond analysis, while providing informative case studies from well-known private and government organizations.